2010
DOI: 10.1002/ijc.25563
|View full text |Cite
|
Sign up to set email alerts
|

Cilengitide inhibits progression of experimental breast cancer bone metastases as imaged noninvasively using VCT, MRI and DCE‐MRI in a longitudinal in vivo study

Abstract: The aim of this study was to investigate the effect of inhibiting a v b 3 /a v b 5 integrins by cilengitide in experimentally induced breast cancer bone metastases using noninvasive imaging techniques. For this purpose, nude rats bearing established breast cancer bone metastases were treated with cilengitide, a small molecule inhibitor of a v b 3 and a v b 5 integrins (75 mg/kg, five days per week; n 5 12 rats) and compared to vehicle-treated control rats (n 5 12). In a longitudinal study, conventional magneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
68
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 56 publications
3
68
1
Order By: Relevance
“…In line with this observation, our data showed that α v β 3 /α v β 5 inhibition by cilengitide resulted in a significant decrease in proliferation of MDA-MB-231 cells in vitro. Correspondingly, previous studies have suggested a direct anti-tumor activity of this compound (14,16,30) and the growth of well-established bone metastases was found to decrease by cilengitide (20). We previously confirmed that α v β 5 is the primary α v integrin expressed in MDA-MB-231 cells suggesting that the anti-tumor effect occurred due to the inhibition of this integrin rather than α v β 3 (20).…”
Section: A B Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…In line with this observation, our data showed that α v β 3 /α v β 5 inhibition by cilengitide resulted in a significant decrease in proliferation of MDA-MB-231 cells in vitro. Correspondingly, previous studies have suggested a direct anti-tumor activity of this compound (14,16,30) and the growth of well-established bone metastases was found to decrease by cilengitide (20). We previously confirmed that α v β 5 is the primary α v integrin expressed in MDA-MB-231 cells suggesting that the anti-tumor effect occurred due to the inhibition of this integrin rather than α v β 3 (20).…”
Section: A B Discussionsupporting
confidence: 69%
“…Correspondingly, previous studies have suggested a direct anti-tumor activity of this compound (14,16,30) and the growth of well-established bone metastases was found to decrease by cilengitide (20). We previously confirmed that α v β 5 is the primary α v integrin expressed in MDA-MB-231 cells suggesting that the anti-tumor effect occurred due to the inhibition of this integrin rather than α v β 3 (20). However, the observed reduction in soft tissue component volumes after adjuvant cilengitide treatment may also be a consequence of the anti-angiogenic effect resulting from the inhibition of α v β 3 and α v β 5 on the endothelial of tumor vessels (14).…”
Section: A B Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…TSU68, a small molecule inhibiting VEGFR1, PDGFRβ and FGFR1 has been shown to suppress CXCL1/CXCR2-dependent niche formation in the liver by inhibition of the inflammatory response through reduction of CXCL1 and IL12 (137). Furthermore, antibodies directed against αv on breast cancer cells prevented metastasis to other organs, but not to the lung (138,139,140). However, a serious limitation for translational research is the complexicity of pre-metastatic and metastatic niches with respect to its architecture and the interplay between secreted factors and cellular components, resulting in difficulties in setting up in vitro systems for its recapitulation for discovery of inhibitory molecules.…”
Section: Translational Aspectsmentioning
confidence: 99%
“…24,26 Most recently, cilengitide has been shown to reduce the size of breast cancer bone metastases in a nude rat model and increase blood vessel permeability on dynamic contrast enhanced magnetic resonance imaging (DCE-MRI). 27,28 ILP with melphalan and TNF is used as salvage therapy in patients with distributed malignant melanoma or soft tissue sarcoma, and a response rate of 76% has been reported in locally advanced soft tissue sarcoma. 29 We have previously shown in the ILP system that the alkylating agent melphalan primarily induces tumor cell death while TNF inflicts tumor vascular damage and endothelial cell death.…”
mentioning
confidence: 99%